Pollutant Removal from Wastewater at Different Stages of the Tanning Process by Electrocoagulation - Alejandra de la Luz-Pedro; Efraín F. Martínez Prior; M. H. López-Araiza; S. Jaime-Ferrer; A. Estrada-Monje; Jennifer A. Bañuelos (Journal of Chemistry)
The removal of chemical oxygen demand (COD), total organic carbon (TOC), turbidity, and chromium content from tannery wastewater at different stages of the process was experimentally investigated using electrocoagulation (EC) with iron and aluminium electrodes. In the EC of the beamhouse wastewater (S1), the effects of initial pH and current density were analyzed and electrical energy consumption was determined. The COD and TOC in the solution were effectively removed, with an initial pH 7.0, using either metallic electrode. With a current density of 28 mA/cm2 for an electrolysis procedure of 60 minutes, the removal efficiency of COD and TOC was 72% and 57% with aluminium electrodes and 69% and 60% with iron electrodes, respectively. The minimum energy consumption for the highest COD and TOC removal was 0.37 and 0.69 kWh/m3 when employing iron or aluminium electrodes, respectively. At the optimal conditions, removal efficiencies close to 100% for turbidity and chromium content for wastewaters S1-beamhouse, S2-tanning, S3-retanning, and S4-a mixture 1 : 1 : 1 (v/v/v) were achieved. Results show that a pseudosecond-order rate equation provides a good correlation for the removal rate of the parameters. Finally, the results indicate that for tannery wastewater, the EC process does not depend noticeably on the electrode material, but that the stage of the tanning process of wastewater sample has the principal effect on treatment efficiency.